Ukuran Kantor Akuntan Publik Dan Opini Audit : Audit Report Lag - Eka Setiajatnika; Trida Gunadi; Alif Muhtadi Ihsan (Coopetition : Jurnal Ilmiah Manajemen, 2022)
This study aims (1) to determine the effect of the size of a public accounting firm (KAP) on audit report lag, (2) to determine the effect of audit opinion on audit report lag and (3) to determine the effect of the size of a public accounting firm (KAP) and audit opinion on audit report lag. Research respondents are members of KAP Ernst & Young, KAP Deloitte, KAP Made Sudarma, Thomas & Dewi totaling 35 respondents. Based on the results of the study that (1) The size of the Public Accounting Firm (KAP) has a positive and significant influence on the Audit Report Lag, (2) That the Audit Opinion has a positive and significant influence on the Audit Report Lag and (3) That the Size of the Public Accounting Firm (KAP) and Audit Opinion have a positive and significant influence on the Audit Report Lag.